French Immersion for English Language Learners?: Kindergarten Teachers’ Perspectives - Mady, Callie (Alberta Journal of Educational Research, 2017)
Given the increasingly diverse, multilingual student body in Canada, the call for increased inclusion in education, and in light of research highlighting the potential for inclusion in French immersion (FI) to be limited by gatekeepers, this study examines the beliefs of kindergarten teachers regarding the inclusion of English language learners in French immersion where entry begins in Grade 1. The theory of planned behavior as discussed by Ajzen (2005) served as a theoretical lens through which the data were examined. In particular, through their responses to a mixed format questionnaire, including a 12 item Likert scale of agreement and open-ended questions, kindergarten teachers revealed that a) French immersion is not for everyone, and b) may be disadvantageous to English language learners in particular. The teachers grounded their beliefs in the importance and influence of English on students’ future endeavours. Beliefs that FI is not for all students were supported by the board’s provision of information to parents as revealed by a document analysis. Such findings highlight the need for information sharing on multilingual language acquisition to extend beyond administrators to include parents and additional educators who have the potential to influence parents’ choices for their children. Compte tenu du corps étudiant canadien de plus en plus diversifié et plurilingue, de la demande pour une intégration accrue en éducation et de la recherche soulignant la possibilité que des gardiens limitent l’inclusion en immersion française, cette étude examine les croyances des enseignants de maternelle face à l’inclusion en immersion française d’élèves apprenant l’anglais (où l’apprentissage du français commencerait en 1re année). La théorie du comportement planifié telle que proposée par Ajzen (2005) a servi d’optique théorique pour l’analyse des données. Les résultats d’un questionnaire à 12 items (réponses sur une échelle de Likert et questions ouvertes) ont indiqué que, entre autres, les enseignants de maternelle croient: a) que l’immersion française n’est pas pour tout le monde et b) que les apprenants de l’anglais pourraient y être particulièrement défavorisés. Les croyances des enseignants reposaient sur l’importance et l’influence de l’anglais dans l’avenir des élèves. Une analyse documentaire a révélé que les croyances selon lesquelles l’immersion française n’était pas pour tous les élèves étaient appuyées par des informations remises aux parents de la part du conseil. Ces résultats soulignent la nécessité d’un partage d’informations sur le plurilinguisme et l’acquisition des langues au delà des administrateurs de sorte à inclure les parents et d’autres enseignants susceptibles d’influencer les choix que font les parents à l’égard de leurs enfants.